X-Sat bus development - Arichandran, K. (2008)
The report would begin with an overview of the work that has to be done in the planning of any satellite mission. Here the work is governed by System engineering processes such as SRR (System Requirements Review) followed by SDR (System Definition Review). The latter, would define the sub-systems and their functional characteristics and their inter dependence. This would be followed by the development of the first version of the sub- system prototypes of the satellite. At the end of this phase, a PDR (Preliminary Design Review) is held to modify and confirm the designs that would function reliably and satisfy the system requirements (as defined by SRR). Following PDR the designs are refined and satellite is fabricated and this would essentially represent the functional model of the satellite that is to be launched.